HUMAN RESOURCE MANAGEMENT IN IMPROVING THE QUALITY OF KINDERGARTEN TEACHERS THROUGH QIRA'ATI METHOD TRAINING - Fiantini, Irawati; Rifa’i, Moh; Jannah, Ulfa Qomariatul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study investigates how human resource management can enhance teacher competence through Qira'ati method training at Integrated Islamic Kindergarten (TK Islam Terpadu) Kraksaan Probolinggo. The research adopts a descriptive qualitative approach with a case study design. Data was collected through interviews, observations, and documentation, with informants consisting of the school principal and three teachers selected using purposive sampling. Data analysis was conducted based on the Miles and Huberman framework, including data presentation, reduction, and conclusion drawing. The study results indicate that teacher training activities, mainly through the Qira'ati method, improve teacher competence at TK Islam Terpadu Kraksaan. This training introduces new teaching techniques and enhances teachers' understanding and skills in implementing the Qira'ati method in their teaching practices. By providing training that aligns with the educational needs at TK Islam Terpadu, it is expected that the quality of teachers will improve, positively impacting the teaching and learning process and developing students' character. This study contributes to understanding the importance of human resource management in optimizing teacher competence through structured and relevant training programs that address the educational needs at the kindergarten level.